Modos de participar: interferências e irreverências estudantis no IFES - Campus Serra - Laurindo, Cynthia Krüger Quinino Marciano (2020)
This paper aimed at following students’ ways of participation as well as their interferences on formation and management processes at Ifes - Campus Serra. The campus offers professional and technological education in a city built up in the midst of many popular fights and movements in the face of inequality, poverty and diverse kinds of violence, processes experienced by its citizens on a regular basis. Thus we propose to research the participation processes from the concept of participation as the exercise of taking part in decision-making processes, both in a State level as well as in our everyday life. The path of this work was taken from the intervention research referential and happened through conversation weaves, during the year 2019, with: two members of social movements in Serra who have experienced urban expansion in this town; students from Ifes, Campus Serra who, inspired by the snowball technique, indicated other subjects; school workers. The research allowed access to a wealth of participation movements and “moves” which take place out of the formal students’ participation channels, even though they still happen on these grounds. We highlight actions like the newspaper No Muro, The Student Guild Edson Luís, the students’ actions at the Welcoming Project and the Cultural Party, for instance, the play “Cinderello”. Finally, we conclude that these ways of participation may interfere on formation and management processes at Ifes and put daily practices - usually silenced at the school everyday life - into analysis.